Diagnóstico de estudantes de uma turma de EJA com TDE e CLOZE - PINHEIRO, Edna Maria Alfaia (2020)
This paper reports part of a teaching experience during the supervised internship course, of the Integrated Licenciatura course in Science, Mathematics and Languages of the Federal University of Pará, in a night class, the first stage of the EJA, a school in the city of Belém. Ten students of the group are described, diagnosing the level of learning of reading and writing skills and calculations of each of them through a standardized school performance test (TDE) and a Cloze about healthy eating.